19. Cortical hyperexcitability in ALS: A heterogeneous process. Issue 3 (March 2016) - J. van den Bos, Mehdi A.; Menon, Parvathi; Geevasinga, Nimeshan; Kiernan, Matthew C.; Vucic, Steve
Abstract : Objective: Cortical hyperexcitability, as heralded by reduced short interval intracortical inhibition (SICI) has been identified as an intrinsic feature of amyotrophic lateral sclerosis (ALS). However, in approximately 20% of patients cortical excitability may be normal, suggesting the presence of pathophysiological heterogeneity. Consequently, the present study assessed for the presence of clinical, functional and neurophysiological differences in ALS phenotypes, as defined by cortical hyperexcitability. Methods: Cortical excitability was assessed in 62 ALS patients. Clinical, functional and neurophysiological parameters were compared between ALS patients with cortical hyperexcitability (SICI  <  5.5%) versus those with a "normal" level of cortical excitability (SICI  >  5.5%). Results: In ALS patients with features of cortical hyperexcitability, there appeared to be an absence of SICI in the early phase (interstimulus interval [ISI] 1–3 ms) with a transition to facilitation at later ISIs (3.5–7 ms). In contrast, ALS patients with normal SICI demonstrated similar levels of inhibition across early and late SICI phases. Of further relevance, ALS patients with abnormal SICI exhibited increased mortality in follow-up. Conclusion: Dysfunction in cortical inter-neuronal circuits probed by short latency paired-pulse TMS appears to capture some of the pathophysiological heterogeneity in ALS and may have direct implications for survival.